Quality of Using Watermelon Extract Substitution for Sweet Bread - Putri, Novari Hasukma; Anggraini, Ezi; Elida, Elida; Yasih, Fitri (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Bread is a food product that is quite popular in Indonesia. Bread is a source of energy that is beneficial to the body when consumed. The main ingredients in making bread consist of wheat flour, water, baker's yeast, and salt. In addition, there are also additional ingredients such as milk, butter, eggs, sugar, delicious ingredients in the form of chocolate and others depending on the type of bread. This study aims to analyze the influence of watermelon extract substitution of 25%, 50%, 75% on the quality of color, aroma, texture, taste, and shape in the sweet bread produced. The type of research used in this study is a pure experiment (True Experiment) with the research design used is a complete random design (RAL) with 3 repetitions. The type of data used was primary data obtained directly from 3 limited panelists by filling out an organoleptic test format. For hypothesis testing, this study uses an analytical test (ANAVA), if it is different, it will be tested with the Ducan Multi Rangers Test (DMRT). Based on the results of the organoleptic test and followed by the statistical test or variant analysis test (ANAVA) showed that there was a significant influence on the quality of the golden brown outer color, the inner color of orange, the quality of the fragrant aroma of watermelon, the quality of smooth texture, the quality of soft texture, the quality of sweetness and taste of watermelon, and the quality of the volumetric shape Ho was accepted by f calculus, < f table. And the results of the organoleptic test were best obtained in treatment 4 (75%).